Growth Performance and Carcass Yield of Broiler Finishers Fed Diets Having Partially or Wholly Withdrawn Fish Meal - Yisa, A.G.; Edache, J.A.; Udokainyang, A.D.; Iloama, C.N. (International Journal of Poultry Science, 2013)
A four-week study was conducted to investigate the effect of partially or completely withdrawing fish meal from broiler finisher diets on growth performance and carcass yield. In a completely randomized design, ninety six (96) four-week-old Marshall Breed of broilers were allotted to four dietary treatments having 0, 50, 75 and 100% of their fishmeal content withdrawn. Each dietary treatment had 24 birds with 3 replicates of 8 birds. Results show that initial weights, final weights, average daily feed intake, average daily weight gain, feed conversion ratio and feed cost per kilogram gain were not negatively affected (P>0.05) by levels of fish meal withdrawal. Dressing percentages were also not significantly different (P>0.05) between treatment means. However, the percent carcass cut-up parts of breast, wings, thighs and drumsticks to live weight of birds fed diets with fish meal totally withdrawn were significantly less (P